Practical Recommendations for Therapeutic Drug Monitoring of Kinase Inhibitors in Oncology. Issue 5 (7th September 2017) - Verheijen, Remy B.; Yu, Huixin; Schellens, Jan H.M.; Beijnen, Jos H.; Steeghs, Neeltje; Huitema, Alwin D.R.
Abstract : Despite the fact that pharmacokinetic exposure of kinase inhibitors (KIs) is highly variable and clear relationships exist between exposure and treatment outcomes, fixed dosing is still standard practice. This review aims to summarize the available clinical pharmacokinetic and pharmacodynamic data into practical guidelines for individualized dosing of KIs through therapeutic drug monitoring (TDM). Additionally, we provide an overview of prospective TDM trials and discuss the future steps needed for further implementation of TDM of KIs.